Cognitive reappraisal moderates the relationship between PTSD symptoms and alcohol use over time in post-9/11 U.S. military veterans. (1st October 2018) - Aase, Darrin M.; Gorka, Stephanie M.; Greenstein, Justin E.; Proescher, Eric; Crane, Natania A.; Everett, Llashe-Kaye; Hassan, Ikram; Osborn, Amanda; Schroth, Christopher; Kennedy-Krage, Amy; Phan, K. Luan
Highlights: Seventy-one post-9/11 veterans were evaluated at least three times over 12 months. Measures of alcohol use, post-traumatic stress disorder (PTSD) symptoms, and emotion regulation were completed. PTSD symptoms were associated with greater alcohol use. At low reappraisal, greater PTSD symptoms were associated with more alcohol use. There was no association between PTSD symptoms and alcohol use at high reappraisal. Abstract: Background: Rates of comorbid alcohol use disorder (AUD) and posttraumatic stress disorder (PTSD) are increasing among post-9/11 veterans, and emotion regulation problems have been identified as a feature of both disorders. However, no studies to date have explored how individual differences in emotion regulation may moderate the relationship between PTSD symptoms and alcohol use. We evaluated how two core emotion regulation strategies – one adaptive (i.e., cognitive reappraisal) and one maladaptive (i.e., expressive suppression) are related to PTSD symptoms and alcohol use over one-year. Methods: A total of 71 post-9/11 veterans (12 female, 59 male) completed a baseline screening and at least two follow-up assessments over the course of 12 months which included measures of emotion regulation, PTSD symptoms, and alcohol use. A mixed growth model was utilized to determine if changes in PTSD symptoms covaried with alcohol use over time and whether this relation was moderated by frequency of use of emotion regulation strategies. Results: In general, higher PTSD symptoms were significantly associated with greater alcohol use, but cognitive reappraisal moderated this relationship. Specifically, at low cognitive reappraisal, greater PTSD symptoms were associated with greater alcohol use. At high cognitive reappraisal, there was no significant association between PTSD symptoms and alcohol use. Conclusions: Findings from the present study suggest that baseline individual differences in cognitive reappraisal influence the relation between PTSD symptoms and alcohol use. For post-9/11 veterans, high levels of cognitive reappraisal may serve as a protective factor against ongoing alcohol use.